The Effect of Using Interactive Whiteboard in EFL Context - Raden Roro Almira Muhammad Adrini; Yuna Tresna Wahyuna (Jurnal Ilmiah Wahana Pendidikan, 2023)
Technology-based innovations provide particular challenges and opportunities via the trustworthy adoption of Information and Communication Technologies (ICTs) and CALL applications whereby technology can be used to improve the learning environment for teachers and students simply because the goal is to create learning environments where students are actively engaged in the learning process. Interactive White Board (IWB) is one example of such emerging technologies. This smart board is an interactive board resembling to conventional white board but connectable electronically to laptops, personal computers, etc. This article aims to explore and analyze the effect of interactive whiteboards as instruments for teaching English as a foreign language. The results of the study provided some evidence that teachers and students have positive attitudes towards the use of IWBs for teaching EFL. The use of Interactive Whiteboard in the teaching of English can be recommended as likely to be more effective for teaching English language, in terms of the formal and lexical aspects of English language learning at EFL context.